A simple route to preparing γ-Fe2O3/RGO composite electrode materials for lithium ion batteries - Xu, Binghui; Guan, Xianggang; Zhang, Lian Ying; Liu, Xiaowei; Jiao, Zhengbo; Liu, Xuehua; Hu, Xiaoqi; Zhao, X. S (Journal of materials chemistry. A, Materials for energy and sustainability, 2018)
A simple approach to synthesizing γ-Fe 2 O 3 nanoparticles encapsulated by reduced graphene oxide (RGO) sheets is demonstrated for the first time. It was found that iron metal can substantially reduce few-layer graphene oxide (GO) to form reduced graphene oxide (RGO) in GO aqueous suspension under ambient conditions, and in the meantime be oxidized to form γ-Fe 2 O 3 nanoparticles dispersed on the surface of RGO sheets. The γ-Fe 2 O 3 /RGO composite delivered both stable cycling performance and good rate capability when used as an anode in a lithium-ion battery cell. This novel experimental method for synthesizing γ-Fe 2 O 3 /RGO composite materials is cost-effective, eco-friendly and suitable for synthesizing other metal oxide/RGO composite materials. A simple approach to synthesizing γ-Fe 2 O 3 nanoparticles encapsulated by reduced graphene oxide (RGO) sheets is demonstrated for the first time.